Cement-based stabilization/solidification of oil refinery sludge: Leaching behavior of alkanes and PAHs - Karamalidis, Athanasios K.; Voudrias, Evangelos A. (Journal of hazardous materials, 2007)
Stabilization/solidification is a process widely applied for the immobilization of inorganic constituents of hazardous wastes, especially for metals. Cement is usually one of the most common binders for that purpose. However, limited results have been presented on immobilization of hydrocarbons in cement-based stabilized/solidified petroleum solid waste. In this study, real oil refinery sludge samples were stabilized and solidified with various additions of I42.5 and II42.5 cement (Portland and blended cement, respectively) and subject to leaching. The target analytes were total petroleum hydrocarbons, alkanes and 16 polycyclic aromatic hydrocarbons of the EPA priority pollutant list. The experiments showed that the waste was confined in the cement matrix by macroencapsulation. The rapture of the cement structure led to the increase of leachability for most of the hydrocarbons. Leaching of n-alkanes from II42.5 cement-solidified samples was lower than that from I42.5 solidified samples. Leaching of alkanes in the range of n-C 10 to n-C 27 was lower than that of long chain alkanes (> n-C 27), regardless the amount of cement addition. Generally, increasing the cement content in the solidified waste samples, increased individual alkane leachability. This indicated that cement addition resulted in destabilization of the waste. Addition of I42.5 cement favored immobilization of anthracene, benzo[ a]anthracene, benzo[ b]fluoroanthene, benzo[ k]fluoroanthene, benzo[ a]pyrene and dibenzo[ a, h]anthracene. However, addition of II42.5 favored 5 out of 16, i.e., naphthalene, anthracene, benzo[ b]fluoroanthene, benzo[ k]fluoroanthene and dibenzo[ a, h]anthracene.